1992
DOI: 10.1007/bf00009375
|View full text |Cite
|
Sign up to set email alerts
|

The decline in N2 fixation rate in common bean with the onset of pod-filling: Fact or artifact

Abstract: It is not clear to what extent genetic, environmental and measurement factors are responsible for the commonly reported decline in nitrogenase activity with the onset of pod-filling in grain legumes. We address this question by observing nitrogenase activity and assimilate partitioning throughout the life span of an indeterminate variety of common bean (GN 1140) under controlled-environment and field conditions. Nitrogenase activity per plant was maintained well into pod-filling in GN 1140 under high-light con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 37 publications
3
12
0
1
Order By: Relevance
“…Soil inoculation induced the formation of 40% more nodules than seed-applied inocula, and this increased nodulation was found to be essentially due to a higher number of small nodules. Moreover, as previously observed (Wadisirisuk et al 1989;Vikman and Vessey 1992), soil inoculation favoured the nodulation on secondary roots. This could be explained by a more uniform distribution and positioning of rhizobia that encounter lateral roots when using soil inoculation (Kyei-Boaben et al 2002;Lopez-Garcia et al 2009).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Soil inoculation induced the formation of 40% more nodules than seed-applied inocula, and this increased nodulation was found to be essentially due to a higher number of small nodules. Moreover, as previously observed (Wadisirisuk et al 1989;Vikman and Vessey 1992), soil inoculation favoured the nodulation on secondary roots. This could be explained by a more uniform distribution and positioning of rhizobia that encounter lateral roots when using soil inoculation (Kyei-Boaben et al 2002;Lopez-Garcia et al 2009).…”
Section: Discussionsupporting
confidence: 75%
“…In field experiments, solid or liquid rhizobial inoculants applied in soil allowed greater nodulation and survival of introduced rhizobia than inoculants applied to seeds, especially under adverse environmental conditions (Brockwell et al 1980). Other experiments showed that seedapplied inoculum led to predominant nodulation at the crown level whereas soil applied inoculants, which allow rhizobia to reach deeper levels of the root zone, induced later nodulation of lateral roots (Wadisirisuk et al 1989;Vikman and Vessey 1992). Moreover, inoculants applied in soils (seed furrow) significantly improved yield and quality of chickpea (Cicer arietinum L.) (Kyei-Boahen et al 2002) while with soybean, yield and grain N content were not significantly increased (Lopez-Garcia et al 2009).…”
Section: Introductionmentioning
confidence: 96%
“…A redução no número de nódulos observada entre 45 e 59 DAE no segundo experimento, mais intensa nas plantas oriundas de sementes com alto teor de Mo (Quadro 2), reforça esta hipótese. Há evidências de que a redução da fixação biológica de N no estádio de enchimento das vagens ocorre principalmente com estresse, afetando mais intensamente o crescimento nodular que a atividade da nitrogenase (Vikman & Vessey, 1992 (Brodrick et al, 1992). Vieira et al (1998a) relataram que a aplicação foliar de Mo aos 25 DAE no campo aumentou a atividade da nitrogenase, e propuseram que o efeito do Mo aplicado via foliar ocorresse principalmente através da manutenção de períodos mais extensos de fixação biológica de N. Sendo assim, a menor nodulação das plantas oriundas de sementes com alto teor de Mo aos 49 DAE teria sido compensada por maior atividade da nitrogenase por unidade de massa nodular, resultando em maior acumulação de N (Quadro 1).…”
Section: Discussionunclassified
“…The acetylene-reduction activity of root nodule, however, was low at later growth stages. The nitrogenfi xing activity of the whole root system declines during the pod-fi lling stage in legume crops (McDermott and Graham, 1989;Vikman and Vessey, 1992) because of the competition for photosynthate between pods and root nodules (Sinclair, 2004). Such competition should occur at a later growth stage in this study.…”
Section: Nodule Size As a Possible Index Of Nitrogen-fi Xing Activitymentioning
confidence: 99%